EKSISTENSI TOKE DALAM JUAL BELI TERNAK DI PASAR TERNAK AGROPOPLITAN GUNUNG MEDAN KENAGARIAN GUNUNG MEDAN KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Naufal Raid (Jurnal Public Administration, Business and Rural Develoment Planning, 2019)
The existence of Javanese toke and Minang toke in the livestock market of Agropolitan Gunung Medan is a unique feature of livestock markets in other Minangkabau areas. The Javanese toke was able to survive while the Minang toke slowly disappeared and was replaced by a toke that came from the Javanese tribe. The purpose of this study was to see the tendency of the survival of the Javanese gecko and the persistence of the Minang gecko in the Agropoplitan Livestock Market, Mount Medan, Kenagarian, Mount Medan, Sitiung District, Dharmasraya Regency. This research is a qualitative research with an intrinsic case study type. This research was conducted at the Agropoplitan livestock market in Mount Medan, Kenagarian, Mount Medan, Sitiung District, Dharmasraya Regency. Informants from this study consisted of livestock toke, livestock market officers, livestock buyers, breeders and local communities. Data collection techniques by means of interviews, documentation and direct observation in the field. While the data analysis used in this study is the analysis of Milles Huberman. The results of this study found that the Javanese toke tend to exist more than the Minang toke because the social capital owned by the Javanese toke is higher than the social capital market of the Minang toke. The level of trust and discipline of the Javanese toke is the main capital in winning the contestation in this Agropolitan livestock market. Social capital is one of the determinants in increasing the existence of the Javanese toke in the agropolitan livestock market arena of Gunung Medan. Toke Jawa is able to build and form a social network based on friendship so that Toke Jawa always survives. This research is expected to add to the scientific treasures in the social field. Social capital can be an important thing in showing a person's existence in society. The government and the community in Dharmasraya Regency should be more active in developing the Gunung Medan Agropolitan livestock market, Dharmasraya Regency